Islamic heritage architecture and art II - Passerini, G. (WIT transactions on the built environment ;, 2018)
Papers presented at the 2nd International Conference on Islamic Heritage Architecture and Art are contained in this volume. The papers deal with the design of many types of buildings in Islamic countries, including not only the better known public buildings like mosques, citadels and forts, but also houses, engineering works, and many others.